2018
DOI: 10.5433/1679-0359.2018v39n1p157
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Mycobacterium bovis in cattle slaughtered from an abattoir in Garanhuns, Pernambuco

Abstract: Tuberculosis is a chronic infectious disease caused by the Mycobacterium tuberculosis complex (CMT), members including M. bovis. The sanitary inspection in slaughterhouses has a great importance on public health for the removal of contaminated meat with pathological lesions. Cattle slaughtered in the abattoir of Garanhuns were subjected to macroscopic, histological, bacteriological, and molecular analyses. Lung inspection revealed gross lesions suggestive of tuberculosis. The characterization of tuberculous gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Bovine tuberculosis predominantly affects cattle and buffaloes, but may occasionally infect other mammalian species, including humans (Etchechoury et al, 2010;Silva et al, 2018). It may spread through direct contact with infected animals, causing the spread of disease among herds or herds to wild animals and vice versa (Corner, Murphy, & Gormley, 2011;Reis, 2015), or being transmitted through indirect contact with contaminated equipment, water and food (Palmer, 2013;Smith, Tauer, Schukken, Lu, & Grohn, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine tuberculosis predominantly affects cattle and buffaloes, but may occasionally infect other mammalian species, including humans (Etchechoury et al, 2010;Silva et al, 2018). It may spread through direct contact with infected animals, causing the spread of disease among herds or herds to wild animals and vice versa (Corner, Murphy, & Gormley, 2011;Reis, 2015), or being transmitted through indirect contact with contaminated equipment, water and food (Palmer, 2013;Smith, Tauer, Schukken, Lu, & Grohn, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Different organs including lungs, lymph nodes, intestines, liver, spleen and heart have been used in previous abattoir surveys for BTB (Müller et al, 2008;Cardoso et al, 2009;Proano-Perez et al, 2011;Gizaw et al, 2017;Yahyaoui-Azami et al, 2017;Silva et al, 2018b). Among these organs, the highest number of BTB positive cases were associated with lung and lymph node lesions (Sa'idu et al, 2015b;Silva et al, 2018b). The presence of lung lesions had the strongest association with the detection of M. bovis infection by PCR (Sa'idu et al, 2015b;Silva et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…Among these organs, the highest number of BTB positive cases were associated with lung and lymph node lesions (Sa'idu et al, 2015b;Silva et al, 2018b). The presence of lung lesions had the strongest association with the detection of M. bovis infection by PCR (Sa'idu et al, 2015b;Silva et al, 2018b). Cranial lung lobes are commonly associated with pulmonary lesions of BTB (Menin et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced number of M. bovis isolates have also been observed in studies that bacteriologically evaluated both lesions suggestive of BTB and nonspecific lymphadenitis during postmortem examination (Furlanetto et al 2012, Alzamora Filho et al 2014a. Considered the gold standard for BTB diagnosis, higher isolation rates are expected in bacteriological culture, with mycobacterial growth rates that can vary from 60.0 (Nassar et al 2007) to 68.75% (Silva et al 2018) of the suggestive lesions. In contrast, despite the low frequency of positive samples verified in the present study, ZN staining revealed AARB + in 100% of the isolates, confirming the high identification specificity of the mycobacterial method (Corner 1994).…”
Section: Discussionmentioning
confidence: 99%